Advanced Synthesis on Lead‐Free KxNa(1−x)NbO3 Piezoceramics for Medical Imaging Applications. Issue 16 (7th February 2018) - Garroni, Sebastiano; Senes, Nina; Iacomini, Antonio; Enzo, Stefano; Mulas, Gabriele; Pardo, Lorena; Cuesta‐Lopez, Santiago
Abstract : Ultrasonic imaging system is a non‐invasive medical imaging technique that has become one of the most widely used diagnostic tools in modern medicine for detecting prenatal anomalies and deep screening of biological tissues. One of the core components of the ultrasound system is represented by the probe where is located the transducer which produces mechanical energy in response to electrical signals, and conversely, produce electrical signals in response to mechanical stimulus. The ultrasound transducer in the probe is generally made of a piezoelectric ceramic material such as lead zirconate titanate (PZT), which present two important limitations as the presence of toxic material as the lead, and low acoustic impedance ascribable to its high density. For these reasons, it is necessary to focus the research on new eco‐friendly piezoelectric materials with properties comparable with PZT. Among them potassium sodium niobate is considered as a leading lead‐free candidate to replace lead‐based piezoceramics, resulting the most promising. In this review, the most relevant and advanced synthesis approaches and the unique properties of this class of lead‐free piezoceramics are presented in detail. Abstract : In this review, the most relevant and advanced synthesis approaches and the unique properties of the lead‐free KNN piezoceramics used for medical imaging applications have been presented.